Controlling Oxidative Addition and Reductive Elimination at Tin(I) via Hemi‐Lability. (16th December 2021) - Caise, Alexa; Crumpton, Agamemnon E.; Vasko, Petra; Hicks, Jamie; McManus, Caitilín; Rees, Nicholas H.; Aldridge, Simon
Abstract: We report on the synthesis of a distannyne supported by a pincer ligand bearing pendant amine donors that is capable of reversibly activating E‐H bonds at one or both of the tin centres through dissociation of the hemi‐labile N‐Sn donor/acceptor interactions. This chemistry can be exploited to sequentially (and reversibly) assemble mixed‐valence chains of tin atoms of the type ArSnSn(Ar)H n SnAr ( n= 1, 2). The experimentally observed (decreasing) propensity towards chain growth with increasing chain length can be rationalized both thermodynamically and kinetically by the electron‐ withdrawing properties of the ‐Sn(Ar)H‐ backbone units generated via oxidative addition. Abstract : A distannyne supported by a pincer ligand featuring pendant CH2 N i Pr2 arms is capable of reversibly activating E−H bonds at one or both of the tin centres through dissociation of the hemi‐labile N–Sn donor/acceptor interactions. This chemistry can be exploited to sequentially (and reversibly) assemble mixed‐valence chains of tin atoms of the type ArSnSn(Ar)H n SnAr ( n= 1, 2).